PEMBELAJARAN KELOMPOK DALAM MATA PELAJARAN ILMU PENGETAHUAN ALAM (IPA) TERPADU (Studi Situs di SMP Negeri 1 Salatiga) - Handayani , Ima Ari (2011)
The objectives of research are to describe (1) the characteristics of learnin materials in a group of integrated Natural Sciences (IPA) subject at SMP N Salatiga, (2) the interaction characteristics of learning group in natural scienc subjects (IPA) integrated at SMP N 1 Salatiga. This is a qualitative research and an ethnographic design. The research i conducted at SMP N 1 Salatiga. The key informants at school are principals science teachers and students. Methods of data collection used observation, dept interviews, and documentation. Analysis of data used arrangement analysis in sit for description. Validity of data includes the level of confidence (credibility transferability, dependence (dependability), and certainty (conformability). The results of research showed that: (1) the material characteristic o learning group are (a) most of material of learning group is done in practices an learning activities or experiment that is done in laboratory, (b) This material o learning group has difficulty level because there is need an activity to prove it, (c The material of learning group has difficulty because there is need cooperatio between student and the member of group, (d) the material of learning group ca help teacher to solve the problem about the limitation of learning facilities, (e) th material of learning group is developed according to the result that is gained from the student's discussion, observation, and experiment that is done by group. (2 characteristic of student interaction in learning group is including (a) the student is cooperating and helping each other if there is student who less understanding (b) the student is active in giving question, answering the question, and givin their opinion, (c) each group has way or work system and dividing work, (d) ther is take place communication in solving problem of each group, (e) interactio between student and teacher by learning together system with or withou instruction pattern, but with motivation and giving stimulation and also awarenes from each individual in group to doing cooperation.